Sweets as traditional medicine in winter season: An ethnobotanical study in Udaipur city, India - Jain, Vartika (Ethnobotany Research and Applications, 2020)
Background Food as medicine has been part of ancient civilizations and shared among generations as dietary health practices. Sweets are one of the important constituents of meals in India. Many plants are used to prepare sweets. In Udaipur city, Rajasthan, India, some specific sweets are consumed during winter season prepared from plants. No scientific study has been carried out to document the traditional botanical knowledge associated with winter sweets in Udaipur city. Hence, the present study was undertaken. Methods Ethnobotanical surveys were carried out at 11 most popular sweet shops of Udaipur city from October to January, 2018. Semi-structured interviews were conducted with shopkeepers about ingredients, preparation technique of sweets etc. and with the consumers about reasons of purchasing winter sweets. Results In total, 36 plants belonging to 21 angiosperm families were found to be used in preparation of winter sweets. The major traditional winter sweets consumed for health benefits were various kinds of Laddu, Halwa and Milk sweets. These were different from each other in shape, taste, shelf life and plant ingredients. All the consumers unanimously affirmed role of some of the winter sweets as traditional medicine. Conclusions Present study has first time documented different plant species used to prepare winter sweets in Udaipur city. Nutritional and pharmacological potential of some of the plants indirectly supports traditional wisdom behind their use in winter sweets for increasing immunity, treatment of joint pain, arthritis, asthma etc. However, clinical studies are required to recommend the winter sweets as dietary nutraceutical products for the claimed health benefits. Keywords: Health tradition, Laddu, Barfi, Nutraceutical, Jaggery, Almond